2022
DOI: 10.1155/2022/3968494
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Yangxinshi Intervention on Cardiac Fibrosis in Diabetic Cardiomyopathy Based on Network Pharmacology

Abstract: Background. Cardiac fibrosis (CF) is major myocardial change in diabetic cardiomyopathy (DCM). Yangxinshi as a Chinese medicine formula is used to treat cardiovascular diseases. However, the exact effective mechanism of Yangxinshi on CF is still uncertain. Hence, based on the pharmacological network, predicting the active components, potential targets and pathways of Yangxinshi on diabetic fibrosis require to be further studied. Materials and Methods. By using Cytoscape 3.6.0 Bisogenet plug-in, the active comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Cardiovascular disease (CVD) is a serious threat to human health with high mortality and morbidity (Almazán‐Ávila, 2020; Boateng et al, 2017; Kalayinia et al, 2021). Clinical practices have proved that Yangxinshi tablet (YXST) is safe and effective for CVD such as coronary heart disease, angina pectoris, myocardial infarction, hyperlipidemia and hyperglycemia (Kuang et al, 2022; Wu et al, 2020; Zhang et al, 2020). As a traditional Chinese medicine preparation, YXST consists of 13 Chinese herbs: Astragali Radix, Ginseng Radix et Rhizoma, Codonopsis Radix, Salviae Miltiorrhizae Radix et Rhizoma, Angelicae Sinensis Radix, Puerariae Lobatae Radix, Epimedii Folium, Crataegi Fructus, Rehmanniae Radix, Coptidis Rhizoma, Corydalis Rhizoma, Ganoderma and Glycyrrhizae Radix et Rhizoma (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a serious threat to human health with high mortality and morbidity (Almazán‐Ávila, 2020; Boateng et al, 2017; Kalayinia et al, 2021). Clinical practices have proved that Yangxinshi tablet (YXST) is safe and effective for CVD such as coronary heart disease, angina pectoris, myocardial infarction, hyperlipidemia and hyperglycemia (Kuang et al, 2022; Wu et al, 2020; Zhang et al, 2020). As a traditional Chinese medicine preparation, YXST consists of 13 Chinese herbs: Astragali Radix, Ginseng Radix et Rhizoma, Codonopsis Radix, Salviae Miltiorrhizae Radix et Rhizoma, Angelicae Sinensis Radix, Puerariae Lobatae Radix, Epimedii Folium, Crataegi Fructus, Rehmanniae Radix, Coptidis Rhizoma, Corydalis Rhizoma, Ganoderma and Glycyrrhizae Radix et Rhizoma (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic cardiomyopathy (DCM) is a prominent cardiovascular complication of diabetes. 1 The main features of DCM include myocardial fibrosis, myocardial hypertrophy, and cardiac dysfunction, which ultimately lead to heart failure. 2 It is reported that inflammation, mitochondrial dysfunction, oxidative stress, cell autophagy, and metabolic disturbance play a role in the pathogenesis of DCM, and there is a complicated mechanism underlying the process of DCM.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, network pharmacology has emerged as a valuable tool for investigating the intricate mechanisms underlying the efficacy of TCM in complex systems. [14][15][16] In this particular study, network pharmacology and molecular docking analysis were utilized to predict the bioactive ingredients, potential molecular targets, and signaling pathways associated with the hepatoprotective effects of SGF against DILI. The results obtained from this research significantly contribute to a more comprehensive comprehension of the pharmacodynamics and mechanisms of action of SGF in the management of DILI.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, network pharmacology has emerged as a valuable tool for investigating the intricate mechanisms underlying the efficacy of TCM in complex systems. [14–16]…”
Section: Introductionmentioning
confidence: 99%